Ecological conditions of the statutory health resort’s development referred to the imperative of sustainable development − example from the Małopolska region - Dryglas, Diana (Geotourism/Geoturystyka)
The aim of this paper is to analyze the ecological conditions that determine investment decisions in tourism and paratourism infrastructure of the statutory health resorts, and evaluation of the ecological infrastructure on the territory of the statutory health resorts of the Małopolska Voivodeship (District). To achieve this formulated purpose, a diagnostic survey method was used, precisley, the technique of examination of the documents and the method of observation. However, essential research material is based on the processing of data from the Central Statistical Office (CSO).